Organochlorine and organophosphate residues in lettuce and green pepper in Ghana's mega city - Bernard Fei-Baffoe; Ernestina Gawu; Ebenezer Ebo Yahans Amuah; Alfredina Sangber-Dery; Lyndon Nii Adjiri Sackey; Nang Biyogue Douti (Case Studies in Chemical and Environmental Engineering)
Over the last decade, pesticide use in agriculture has helped protect crops but left residues in food, posing health risks. This study analyzed organochlorine (Delta-HCH and Beta-HCH) and organophosphate (chlorpyrifos and dimethoate) residues in lettuce and green pepper from two communities in Ghana. Thirty-one farmers were surveyed, and samples were tested using Gas Chromatography. Chlorpyrifos, found in lettuce from Legon farm at 0.1403–0.2291 mg/kg, exceeded EU and USA Maximum Residue Limits, while green pepper contained no residues. Findings emphasize the need for ongoing pesticide monitoring and public education to ensure food safety and health.